EFETIVITAS TEKNIK MARMET TERHADAP KELANCARAN PENGELUARAN ASI PADA IBU POSTPARTUM DI PRAKTIK MANDIRI BIDAN ROSITA, S.Tr.Keb KOTA PEKANBARU - Heryani Amanah; Komaria Susanti; Wira Ekdeni Aida; Hirza Rahmita (Fakultas Ilmu Kesehatan, 2026)
The breastfeeding process can be done immediately after the baby is born, but the reality in the field shows that many mothers experience ineffectiveness of the breastfeeding process due to low breast milk production in the first days. The purpose of this study is to determine the effectiveness of the Marmet technique on the smoothness of breast milk production in postpartum mothers at the Independent Clinic of Midwife Rosita, S. Tr.Keb, Pekanbaru City. This research method is quantitative using a Quasi Experimental design through a Pretest-Posttest design with a comparison of two groups. The population in this study were all postpartum mothers at the Independent clinic of midwife Rosita, S. Tr.Keb, Pekanbaru City. as many as 20 people, the sampling technique was the purposive population. The results of the study showed that the smoothness of breast milk production before the marmet technique was not smooth for 15 postpartum mothers (75.0%) and after the marmet technique was smooth for 18 postpartum mothers (90.0%). awilcoxon test was then performed, and a p-value of 0.000 < 0.05 was obtained, indicating a significant effect of the marmet technique on breast milk flow. The Marmet technique is effective in increasing breast milk flow in postpartum mothers. Healthcare workers are advised to implement this technique as a non-pharmacological intervention to support successful exclusive breastfeeding.